Academic writing and genre : a systematic analysis - Bruce, Ian, 1953- (Continuum, 2008)
The focus of this book is the use of genre-based approaches to teaching academic writing. Genre-based courses enable second language learners to integrate their linguistic, organisational and contextual knowledge in a variety of different tasks. The book reviews pedagogical approaches to genre through English for Specific Purposes and Systemic Functional Linguistics to present a synthesis of the current research being undertaken in the field. From this theoretical base, Ian Bruce proposes a new model of genre-based approaches to academic writing, and analyses the ways in which this can be impl.